Faktor-Faktor yang Mempengaruhi Kualitas Hidup Anak Usia Sekolah dengan Thalasemia di RSAB Harapan Kita - Nasya Prawesti Sugiarto; Ira Kusumawati; Rahayu Maharani (Jurnal Ilmu Kesehatan dan Gizi, 2026)
Thalassemia is a chronic genetic disease that requires long-term treatment and affects children's quality of life physically, psychologically, socially, and academically due to chronic anemia and regular blood transfusion needs. This study aimed to determine factors influencing the quality of life of children with thalassemia at Rumah Sakit Anak dan Bunda Harapan Kita. A descriptive design with a cross sectional approach was used, involving 41 respondents through total sampling. Data were collected using the Pediatric Quality of Life Inventory (PedsQL 4.0 Generic Core Scale) and respondent characteristics including age, gender, socioeconomic status, parental education, and frequency of blood transfusions. Data were analyzed using univariate and bivariate analysis with the Chi-Square test. The results showed most respondents were under ten years old, female, from families with socioeconomic status below the minimum wage, had parents with high school or higher education, and received blood transfusions every three weeks. Bivariate analysis indicated only the frequency of blood transfusions was significantly associated with quality of life, while other variables were not. Thus, transfusion frequency is the main factor influencing quality of life in children with thalassemia.